ANALISIS DETERMINAN SISTEM INFORMASI E-TICKETING : PENDEKATAN EXTENDED THEORY OF PLANNED BEHAVIOUR - Kinanti, Firsty; Baridwan, Zaki (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to examine the factors that affect intention to use e-ticketing information system and its use the Theory of Planned Behaviour (TPB) as a development of the model used by Karami (2006) and Dehbashi (2007). The method data collection is a survey method. The sample of 86 individuals is the user of e-ticketing onformation system at Juanda International Airport in Surabaya. The data were analyzed by using Partial Least Square (PLS) software. The results of this study indicate that attitude and perceived behavioral control affect the intention to use e-ticketing information system. While subjective norm and trust did not affect the intention to use e-ticketing information system. The implication of this study is relevant to the management of the companyÂ  to be more consider the factors that influence in developing ticketing transactions through the use of e-ticketing information system. Â  Keywords: Theory Planned Behaviour (TPB), e-ticketing, attitude, subjective norm, perceived behavioral control, trust, self efficacy, intention.